THE S-VELOCITY STRUCTURE OF THE EAST ASIAN MANTLE FROM INVERSION OF SHEAR AND SURFACE WAVEFORMS - Friederich W. (My University, 2003)
The structure of the mantle beneath East Asia down to 800 km depth is investigated using full waveforms of seismic shear and surface waves. Epicentral distances are limited to less than 40°. In contrast with previous waveform inversions, we avoid ray-theoretical or path-integral approaches. Instead, we use (1) exact 3-D waveform sensitivity kernels that correctly reflect off-path sensitivity and the existence of Fresnel zones. We apply (2) an accurate 3-D forward modelling technique based on a coupled-mode, multiple-forward-scattering approach, allowing us (3) to iterate the inversion procedure through several 3-D models and (4) to evaluate the true misfit between the data and the synthetics for the 3-D model. Average lateral resolution of the model in regions with good path coverage is 400 km throughout the upper mantle. In the depth range from 100 to 250 km the lateral resolution even approaches 200 km. Since wave front healing is taken into account, the amplitudes of velocity perturbations are larger than in other tomographic models. Moreover, the waveform sensitivity kernels provide an intrinsic physical smoothing of the model, stabilizing the inversion. Finally, owing to the use of exact sensitivities, better resolution can be achieved with a given set of seismograms.
Keywords: East Asia; mantle; mode coupling; scattering; seismic waves; tomography